Pengaruh Kualitas Pelayanan dan Brand Image terhadap Kepuasaan Pelanggan di PT Ztwo Makmur Mandiri - Abizar Faturrohman; Nur Hayati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to measure the extent to which service quality can affect the level of customer satisfaction and the extent to which customer perceptions of brand image can affect their satisfaction with the product or service provided. In addition, this study also aims to analyze the relationship between service quality and brand image in shaping customer satisfaction. Quantitative research was conducted on a population of 150 customers, 67 of whom had subscribed for 3 to 6 months were taken as samples. This study used the Solvin formula to determine the sample size. This study uses primary data collected directly from respondents through distributing questionnaires. The results of this study indicate that service quality and brand image can significantly predict the level of customer satisfaction. The coefficient of determination shows that the combination of service quality and brand image accounts for about 45.4% of customer satisfaction. However, about 54.6% of the variance cannot be explained by service quality or brand image, so there may be other factors that affect customer satisfaction besides these two variables.